The Influence of Corporate Social Responsibility and Green Accounting Implementation on Sustainable Development Goals in Mining Sector Manufacturing Companies Listed on the Indonesia Stock Exchange Period 2022-2024 - Lumban Tobing, Rizki; Mitha Christina Ginting; Gracesiela Yosephine Simanjuntak; Sahala Purba (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2026)
This study aims to examine and analyze the influence of corporate social responsibility and green accounting implementation on sustainable development goals in mining sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2022-2024. The type of sample used is purposive sampling with a total population of 63 mining sector companies and a sample used by the researcher of 12 mining sector companies listed on the Indonesia Stock Exchange through www.idx.co.id. The type of research conducted is quantitative research with the data analysis method used being multiple linear regression analysis. The research results show that partially Corporate Social Responsibility (CSR) has a positive and insignificant significant effect on Sustainability Development Goals (SDGs), Green Accounting has a positive and significant effect on Sustainability Development Goals (SDGs), while simultaneously the variables Corporate Social Responsibility (CSR) and Green Accounting have a significant effect on Sustainability Development Goals (SDGs). The results of the coefficient of determination test for the variables Corporate Social Responsibility (CSR) and Green Accounting on Sustainability Development Goals (SDGs) are able to explain the Sustainability Development Goals (SDGs) variable by 18.1% and the remaining 81.9% is influenced by other variables not included in the regression model of the study.